Effect of herbal feed additives on milk performance and health status of dairy goats - Wójtowski Jacek Antoni; Pikul Jan; Mikołajczak Przemysław; Czopowicz Michał; Kaba Jarosław; Foksowicz-Flaczyk Joanna; Antkowiak Ireneusz; Pytlewski Jarosław; Markiewicz-Kęszycka Maria; Stanisławski Daniel (Journal of Veterinary Research)
Interest is increasing in natural feed additives that improve animal health, raise farming productivity and enhance the quality of animal products. These additives, especially polyphenols, are biologically active chemical compounds found in plants.